2022
DOI: 10.7759/cureus.22056
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Magnetic Resonance Spectroscopy in Predicting the Grade of Glioma Keeping Histopathology as the Gold Standard

Abstract: BackgroundGliomas are the most prevalent intrinsic tumors of the central nervous system and are categorized from grade I to grade IV. Magnetic resonance imaging (MRI) provides exact diagnosis, prognosis, and assessment of tumor response to current chemotherapy/immunotherapy and radiation therapy. With histopathology serving as the gold standard, we aimed to assess the diagnostic accuracy of magnetic resonance spectroscopy (MRS) in predicting glioma grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
(22 reference statements)
3
15
1
Order By: Relevance
“…In their investigation, Mahmud et al discovered MRI specificity and sensitivity of 84 and 75%, respectively, which is close to our findings. It has been demonstrated that including an MR Spectroscopy sequence can increase the diagnosis accuracy of brain malignancies (Rafique et al, 2022). In their investigation, Jesrani et al discovered that sensitivity was 87.5%, specificity was 93.3%, positive predictive value was 95.5%, negative predictive value was 89.7%, and accuracy was 92.1% using MRS, which corresponds to the results observed in our study (Musawar et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…In their investigation, Mahmud et al discovered MRI specificity and sensitivity of 84 and 75%, respectively, which is close to our findings. It has been demonstrated that including an MR Spectroscopy sequence can increase the diagnosis accuracy of brain malignancies (Rafique et al, 2022). In their investigation, Jesrani et al discovered that sensitivity was 87.5%, specificity was 93.3%, positive predictive value was 95.5%, negative predictive value was 89.7%, and accuracy was 92.1% using MRS, which corresponds to the results observed in our study (Musawar et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…5 The diagnosis of localised brain lesions with MRI or CT scan is typically challenging since they have similar appearances most of the time, and it is hard to differentiate neoplastic lesions from non-neoplastic. 6,7 MRS is a non-invasive diagnostic procedure that analyses chemical composition of human tissues. MRS was initially used in therapeutic settings in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic Resonance Spectroscopy (MRS) 2 provide crucial knowledge that can aid in the identification of abnormal conditions. 7 Aim of present research is to determine diagnostic accuracy of MRS for differentiating malignant brain lesions in patients presenting with focal brain lesions. Because existing literature has reported variable diagnostics accuracy of MRS and most of these studies were conducted using small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma, one of the most common central nervous system tumors (CNS), has a five-year survival rate of less than 5% and is widely recognized as a highly malignant tumor ( 1 , 2 ). According to the WHO classification of brain tumors, pathology and clinical practices typically divide gliomas into low and high grades ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%